1923 N.D. Laws 380 - (:unkn) unknown (My University, 1923)
Ch. 266, § 2: Commiting Crime When Armed. If any person shall commit or attempt to commit a crime when armed with a pistol or revolver, and having no permit to carry the same, he shall be in addition to the punishment provided for the crime, be punished by imprisonment for not less than ten years.
Keywords: COMMITTING CRIME W/ WEAPON